Lower Eyelid Laceration in Children: A Case Report: Poster Presentation - Case Report - Ophthalmologist - FRANCISCUS ASSISI TIMMY BUDI YUDHANTARA; FADIMA FITRI LARASATI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Eyelid lacerations may be associated with serious ocular injury and are often accompanied by other ocular injuries. Most injuries occur in children. Eyelids have an important role in protecting the globe. Effective management of eyelid lacerations requires an understanding of the basic anatomical features of the eyelids. Case Illustration : A two-year-old boy was brought to our emergency department after getting scratched in the eyelid by the family dog. The patient has received first aid and a tetanus shot at another hospital. Eye examination shows a lower eyelid laceration on the right eye, extending from the medial downwards around 3 cm. Visual examination was central+, steady+, maintenance+, and eye movement was within normal limits. The patient was admitted to undergo eyelid repair in the operating room. Discussion : The first step in eyelid repair is wound irrigation and removal of foreign particles to avoid infection and inflammation, and primary repair of eyelids should be performed within 12 to 24 hours of the injury to reduce subsequent complications. The recommended method for best wound closure and healing is gently handling tissue edges, slight eversion, and using the smallest diameter sutures. A proper pre-operative assessment and surgical planning include evaluation of the thickness of the defect, the size, the location, and the involvement of canthus and lacrimal drainage. The goals are to provide adequate eye closure, preservation of tear film, maintenance of visual field, and aesthetics. Conclusion : A thorough knowledge of the eyelid anatomy and suture technique is important to successfully repair the defect while maintaining eyelid function.